A modified Perturb & Observe MPPT technique to tackle steady state and rapidly varying atmospheric conditions. (15th November 2017) - Kamala Devi, V.; Premkumar, K.; Bisharathu Beevi, A.; Ramaiyer, S.
Highlights: Here, modified Perturb & Observe technique is used that tackles the issue of conventional Perturb & Observe. The Modified Algorithm subsides unsteady oscillations in PV reference voltage using a different technique that requires reduced instruction sets. It also tackles the issues arising due to rapidly varying solar irradiance and temperature. Abstract: A comparison between two methods of maximum power point tracking for Solar Photovoltaic (PV) is attempted here. A modified method is proposed and evaluated. Perturb & Observe (P&O) method is selected for analysis as this method requires reduced implementation cost with better performance output. A Modified P&O method using directional step size is suggested here that can effectively tackle steady state variations around maximum power point and dynamic variations in environmental conditions of temperature and solar radiation. This is achieved by determining a step size that switches to 'zero' during the above conditions. Thus, the proposed method provides a stable PV voltage. The proposed method is evaluated for performance against the "Hill Climbing" P&O method by using the Ropp, Daily Profile, Irradiance-Temperature and Sunny Day tests. The average efficiency improvement was found to be in the range of 1–1.1% under ideal conditions.